2020
DOI: 10.1177/0097700420969135
|View full text |Cite
|
Sign up to set email alerts
|

The “Bilingual Education” Policy in Xinjiang Revisited: New Evidence of Open Resistance and Active Support among the Uyghur Elite

Abstract: The “bilingual education” policy in Xinjiang has been one of the most contentious policies implemented in the region in recent decades. Given its negative impact on one of the most important markers of Uyghur ethnic identity, it has been a major cause of Uyghur discontent. Nevertheless, our knowledge of the genesis of this policy and the negotiations that took place around its implementation has been partial at best. Through an in-depth analysis of two essays published in the early and mid-2000s by two promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Students wanted to continue Nuosu language learning and did not consider it useless for their future career development. Baranovitch suggested that many Uyghur academics had expressed their opposition to the unbalanced bilingual education, which preferred Mandarin and neglected the Uyghur language [10]. For instance, Uyghur scholar Teklimakani, has repeatedly expressed his concern and anxiety about the Uyghur language and culture's disappearance in his articles and further advocated Uyghurs' determination and practical actions of protecting and promoting their language [10].…”
Section: Bilingual Education Minority Identity and Cultural Diversitymentioning
confidence: 99%
“…Students wanted to continue Nuosu language learning and did not consider it useless for their future career development. Baranovitch suggested that many Uyghur academics had expressed their opposition to the unbalanced bilingual education, which preferred Mandarin and neglected the Uyghur language [10]. For instance, Uyghur scholar Teklimakani, has repeatedly expressed his concern and anxiety about the Uyghur language and culture's disappearance in his articles and further advocated Uyghurs' determination and practical actions of protecting and promoting their language [10].…”
Section: Bilingual Education Minority Identity and Cultural Diversitymentioning
confidence: 99%
“…The assimilationist policy had already been enacted in different minority regions with different pace and intensity depending on state perceptions of each minority group (e.g. Baranovitch, 2020). A year later in August 2021, to speed up assimilation, mandatory Mandarin Chinese teaching was expanded to Mongolian kindergartens with the state's implementation of the “Children Speak in Unison” regulation (Grey & Baioud, 2021a).…”
Section: Inner Mongolia and Shifting Language Policiesmentioning
confidence: 99%